2012
DOI: 10.1111/j.1469-8137.2012.04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiological responses of Solanum nigrum and Solanum torvum to cadmium stress

Abstract: Summary• Under cadmium (Cd) stress, Solanum nigrum accumulated threefold more Cd in its leaves and was tolerant to Cd, whereas its low Cd-accumulating relative, Solanum torvum, suffered reduced growth and marked oxidative damage. However, the physiological mechanisms that are responsible for differential Cd accumulation and tolerance between the two Solanum species are largely unknown.• Here, the involvement of antioxidative capacity and the accumulation of organic and amino acids in response to Cd stress in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(59 citation statements)
references
References 64 publications
2
57
0
Order By: Relevance
“…Plants exposed to toxic metals accumulated specific AAs, which may have beneficial functions and play various roles (Xu et al 2012a, 2012b, Pavlíková et al 2014a. Chaffei et al (2004) suggested that an increase in the proportion of high N:C by AAs, is a protective strategy in plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants exposed to toxic metals accumulated specific AAs, which may have beneficial functions and play various roles (Xu et al 2012a, 2012b, Pavlíková et al 2014a. Chaffei et al (2004) suggested that an increase in the proportion of high N:C by AAs, is a protective strategy in plants.…”
Section: Resultsmentioning
confidence: 99%
“…cumulate specific amino acid (AAs), which may have beneficial functions and play various roles in plants (Xu et al 2012b, Pavlíková et al 2014a.…”
mentioning
confidence: 99%
“…Plants that were exposed to toxic metals have also been shown to accumulate specific AA, which may have beneficial functions. The AA which are accumulated under heavy metal stress, play various roles in plants, including acting as signaling molecules, and osmolytes, regulating ion transport and facilitating detoxification (Xu et al, 2012). Reports of the role of AA in the hyper accumulation of metals by plants are limited.…”
Section: Methodsmentioning
confidence: 99%
“…For example, both PIN2 and AUX1 are required for plant adaptation to alkaline stress. PIN2 induces alkaline stress adaptation via a PKS5-mediated signaling cascade to modulate proton secretion in root tips to maintain primary root (PR) elongation (Xu et al, 2012;. AUX1 is involved in alkaline stressinduced RSA remodeling via ethylene-mediated auxin accumulation .…”
mentioning
confidence: 99%